2021
DOI: 10.1021/acscatal.1c01544
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Catalytic Dearomative Addition of Grignard Reagents to 4-Methoxypyridinium Ions

Abstract: We describe a general catalytic methodology for the enantioselective dearomative alkylation of pyridine derivatives with Grignard reagents, allowing direct access to nearly enantiopure chiral dihydro-4-pyridones with yields up to 98%. The methodology involves dearomatization of in situ-formed N -acylpyridinium salts, employing alkyl organomagnesium reagents as nucleophiles and a chiral copper (I) complex as the catalyst. Computational and mechanistic studies provide insights into the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This transformation gave rise to enantiopure chiral dihydro-4-pyridones 352 in good yields and ee values (Scheme 164, eq 2). 235 A detailed study on the dearomative addition of Grignard reagents to N-alkyl pyridinium electrophiles was carried out by Smith and co-workers in 2020. 236 They found that the regiochemical outcomes had predictable trends associated with the pyridinium substitution patterns.…”
Section: Addition Of Other Nucleophilesmentioning
confidence: 99%
“…This transformation gave rise to enantiopure chiral dihydro-4-pyridones 352 in good yields and ee values (Scheme 164, eq 2). 235 A detailed study on the dearomative addition of Grignard reagents to N-alkyl pyridinium electrophiles was carried out by Smith and co-workers in 2020. 236 They found that the regiochemical outcomes had predictable trends associated with the pyridinium substitution patterns.…”
Section: Addition Of Other Nucleophilesmentioning
confidence: 99%
“…In particular, the dearomative addition to p-methoxypyridinium ions is a very elegant method to prepare dihydropyridone derivatives. 7 The comprehensive study of catalytic transformation mechanisms motivates the research group of Prof. Clark Landis (University of Wisconsin-Madison). He introduced his current research by demonstrating the usefulness of the hydroformylation reaction to construct tertiary and quaternary centers in an asymmetric fashion.…”
Section: Reactivitymentioning
confidence: 99%
“…In particular, the dearomative addition to p -methoxypyridinium ions is a very elegant method to prepare dihydropyridone derivatives. 7…”
Section: Reactivitymentioning
confidence: 99%
“…Dearomatization of nitrogen heteroarenes for the synthesis of saturated azaheterocycles is an attractive approach as it uses commonly available heteroarenes as starting materials and the reaction products, dihydropyridines, can be further functionalized for the synthesis of pyridines, tetrahydropyridines, and piperidines. The addition of various nucleophiles has been achieved, including asymmetric additions for the synthesis of enantiopure dihydropyridines. With regard to asymmetric dearomative arylation of pyridiniums and related heteroarenium salts, recently our group and others have reported that N -alkyl- and N -acylpyridinium salts can undergo asymmetric dearomatization using aryl boronic acids, aryl zinc, and electron rich aryl nucleophiles. ,,,, …”
mentioning
confidence: 99%